QUALITY IMPROVEMENT USING LEAN SIX SIGMA AND FAILURE MODES AND EFFECT ANALYSIS AT PT. CIPTA WARNA PELANGI - Putra , Zam Zam Permana; Sulistiyowati , Wiwik (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
PT. Cipta Warna Pelangi is a service company engaged in printing, which serves the needs and desires of customers related to printing. Products produced by the company include packing, cigarettes, label brochure books, invitations, food boxes, paper bags, letterheads, envelopes, calendars and so on, but still found some products that have defects. In the first three months of the year 2023, namely January, February, and March, a total of 321,175 pieces defects occurred. Then, in the following three months, the defects escalated further to a total of 499,005 pieces. This situation has become a significant concern as the total defects each month continue to increase. As a result, it is necessary to implement corrective measures in order to minimize the defects present at PT. Cipta Warna Pelangi. It is noted that there were 109,650 pieces defects in April 2023, 163,880 pieces defects in May 2023, and 225,475 pieces defects in June 2023. The products that experienced the highest number of defects are offset, spot UV, and die cut. This study aims to help companies determine the value of reject and waste rates using the lean six sigma method; find out the highest RPN value using the Failure Mode and Effect Analysis (FMEA) method. This research uses lean six sigma method to overcome these problems, Lean Six Sigma is a quality control method that is a combination of Lean and Six Sigma. Lean is an approach that is constantly taken with the aim of eliminating waste and increasing the value of the product provided to consumers. Six Sigma is a method used in the manufacturing industry to improve product quality by identifying and minimizing factors or root causes of product defects. FMEA is used to evaluate and analyze the hazard level of any type of failure that may occur in the production process or in the products used by consumers. The results of this research indicate that the waste defect has obtained the first rank among the other seven types of waste, meaning that waste defect is the top priority for improvement. From the FMEA results, varnish damage obtained the highest RPN value of 252, which is caused by inconsistent quality of the UV liquid brand. Therefore, it is recommended to switch to a different brand of UV liquid